Managing the Energy Transition for Sustainable Land Transportation in Indonesia: A Systematic Review of Policy and Socio-Economic Implications for Road and Rail - Samuel Darwisman; Agus Sulistiyono; Aditya Karsa; Wedi Hendra; Siti Maemunah (Dinasti International Journal of Education Management and Social Science, 2025)
Managing the energy transition in the land transport sector is a critical managerial challenge for achieving Indonesia's 2060 Net Zero Emission target. This study aims to identify, synthesize, and evaluate global green energy policies, and to formulate their policy and socio-economic implications for Indonesia's road and railway sectors. A Systematic Literature Review (SLR) methodology, based on the PRISMA 2020 protocol and CASP quality appraisal, was applied to 35 relevant studies published between 2015 and 2025. Thematic analysis identified three primary policy pillars: (1) economic incentives, (2) regulatory mandates, and (3) infrastructure development. This review concludes that effective transition management requires an adaptive hybrid policy framework. The novelty of this research is an evidence-based synthesis that recommends a a multi-modal approach considering socio-economic impacts, prioritizing electrification for light-duty and urban transport while utilizing biofuels for heavy-duty freight and long-haul logistics.